Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/chem.201703009
|View full text |Cite
|
Sign up to set email alerts
|

[UO2Cl2(phen)2], a Simple Uranium(VI) Compound with a Significantly Bent Uranyl Unit (phen=1,10‐phenanthroline)

Abstract: A simple synthesis based on UO Cl ⋅n H O and 1,10-phenanthroline (phen) resulted in the formation of a new uranyl(VI) complex [UO Cl (phen) ] (1), revealing a unique dodecadeltahedron coordination geometry around the uranium center with significant bending of the robust linear arrangement of the uranyl (O-U-O) unit. Quantum chemical calculations on complex 1 indicated that the weak but distinct interactions between the uranyl oxygens and the adjacent hydrogens of phen molecules play an important role in formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 48 publications
8
46
0
Order By: Relevance
“…Rather via a dual ligand strategy that combines coordination and supramolecular chemistry, facilitated by the flexibility of 1,10-phenanthroline molecules and stabilized via the creation of a 'π-pocket' by the 2,4,6-trihalobenzoic acid ligands, we were able to systematically explore structural aspects of uranyl bending. These findings were compared to results from density functional calculations and QTAIM analysis, which indicated that the bending of the uranyl unit has electrostatic origins and is energetically favorable until O-U-O angles reach approximately 162º, thus the uranyl bending described herein and in the recent examples from Hayton et al 37 and Ikeda-Ohno and colleagues 41 likely represent the upper limit of uranyl bending that can be achieved via coordination chemistry pathways.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Rather via a dual ligand strategy that combines coordination and supramolecular chemistry, facilitated by the flexibility of 1,10-phenanthroline molecules and stabilized via the creation of a 'π-pocket' by the 2,4,6-trihalobenzoic acid ligands, we were able to systematically explore structural aspects of uranyl bending. These findings were compared to results from density functional calculations and QTAIM analysis, which indicated that the bending of the uranyl unit has electrostatic origins and is energetically favorable until O-U-O angles reach approximately 162º, thus the uranyl bending described herein and in the recent examples from Hayton et al 37 and Ikeda-Ohno and colleagues 41 likely represent the upper limit of uranyl bending that can be achieved via coordination chemistry pathways.…”
Section: Discussionmentioning
confidence: 79%
“…A recent study from Hayton et al surveyed uranyl bending in hybrid materials and reported that the smallest observed O-U-O angles for the uranyl unit were between 166-168º. 37 In their study, they highlighted three compounds made with the uranyl cation and a 12-membered macrocycle with O-U-O angles between 161.7(5)º and 164.1(3)º, thereby setting a new mark for uranyl bending, which has recently been matched by Ikeda-Ohno et al 41 is comparable to the smallest values reported in the literature by Hayton 37 and Ikeda-Ohno, 41 and represents the most significant uranyl bending we observe in this family of complexes. Comparing the 2,4,6-trifluorobenzoic acid complexes 1 and 4, we note that complex 1 is a 'bent' 1:2 complex with respect to the uranyl cation and both ligands,…”
Section: Description Of Structuresmentioning
confidence: 86%
See 1 more Smart Citation
“…It is possible that a 7, which also features a significantly distorted Oyl-U-Oyl angle (161.8(1)°) ( Figure 3, Table 1). 57 Our X-ray crystallographic analysis of UO2(OTf)2( H N4) (6) and its analogues revealed that the uranyl-pyridinophane interaction is quite weak (as evidenced by the long U-N bond lengths). Thus, attempts to cause further perturbation of the Oyl-U-Oyl angle in uranyl will likely require a stronger interaction between the uranium center and the co-ligands.…”
Section: Steric Perturbation Of the Oyl-u-oyl Anglementioning
confidence: 88%
“…To analyze the geometrica nd electronic effects more deeply when substituting py (2)w ith pic (6)o rl ut (10), quantum chemicalo ptimizations of the respective molecules were performed. All presented electronic structure calculations were done with the software packages Turbomole 7.3.1 [15] and Orca 4.2.1 [16] (for computational details please see the Computational Section).…”
Section: Structural Descriptionmentioning
confidence: 99%